Micro [compact disc, unabridged] : a novel - Crichton, Michael, 1942-2008 (Harper Audio, 2011)
Three men are found dead in the locked second-floor office of a Honolulu building, with no sign of struggle except for the ultrafine, razor-sharp cuts covering their bodies. The only clue left behind is a tiny bladed robot, nearly invisible to the human eye. In the lush forests of Oahu, groundbreaking technology has ushered in a revolutionary era of biological prospecting. Trillions of microorganisms, tens of thousands of bacteria species, are being discovered; they are feeding a search for priceless drugs and applications on a scale beyond anything previously imagined. In Cambridge, Massachusetts, seven graduate students at the forefront of their fields are recruited by a pioneering microbiology start-up. Nanigen MicroTechnologies dispatches the group to a mysterious lab in Hawaii, where they are promised access to tools that will open a whole new scientific frontier. But once in the Oahu rain forest, the scientists are thrust into a hostile wilderness that reveals profound and surprising dangers at every turn. Armed only with their knowledge of the natural world, they find themselves prey to a technology of radical and unbridled power. To survive, they must harness the inherent forces of nature itself.